Direct Transapical Implantation of an Endocardial Pacing Lead to the Left Ventricle: An Alternate Pacing Site After Tricuspid Valve Replacement - ÇİNÇİN, AHMET ALTUĞ; KARARMAZ, ALPER; AK, KORAY; ARSAN, SİNAN (WILEY-BLACKWELL, 2014)
In this paper, we report an alternative approach for implantation of ventricular pacing lead for complete atrioventricular block after tricuspid valve replacement. doi: 10.1111/jocs.12288 (J Card Surg 2014;29:290-292)
Keywords: CARDIAC RESYNCHRONIZATION THERAPY; CORONARY-SINUS LEAD